Spiritual and Psychological Well-Being among Uniformed Personnel in Philippine National Police - del Rosario, Marivic Dimapilis; Hobro Jr., Florentino; Penaranda, Marcus Ralph; Villa, Mon Francis; Villa, Elizabeth Buena (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study aimed to determine the spiritual and psychological well-being among uniformed personnel in Philippine National Police. The descriptive correlational research design was used employing the survey questionnaire distributed randomly to 100 uniform personnel of the PNP province of Cavite. The descriptive statistical tools were used including the percentage, mean, ranking and Pearson-r. The research highlights the significant impact of spiritual and psychological well-being of uniformed police personnel. Regular practices like prayer, meditation, and yoga help maintain balance, concentration, and resilience against adversity. This positive mental health contributes to job satisfaction, morale, and stress reduction. A sense of belonging and camaraderie within the police force also contributes to overall wellbeing. A strong spiritual affiliation can serve as a coping mechanism, enhancing mental well-being and fortitude in challenging professional situations. A positive outlook on life can impact colleagues, work, and obstacles faced in the police force. A strong spiritual foundation provides a sense of identity, purpose, and value, enhancing the effectiveness, satisfaction, and resilience of public sector personnel. Recognizing and addressing this component can improve the effectiveness, satisfaction, and resilience of the police force.